PROFITABILITAS USAHA DAN ELEMEN LAINNYA TERHADAP NILAI PERUSAHAAN - Dinda Sal Sabila; Tjahjono, Rudi Setiadi (E-Jurnal Akuntansi TSM, 2023)
The purpose of this study is to obtain empirical evidence regarding the effect of profitability, solvability, liquidity, firm size, dividend policy, institutional ownership and managerial ownership on firm value. The population used in this research is non-financial companies listed on the Indonesia Stock Exchange (IDX) from 2019 to 2021. The sample used in this research is 59 non-financial companies listed on the Indonesia Stock Exchange. Purposive sampling is a sampling method used with a total of 177 data and to analyze the data using multiple regression analysis. The results of this study indicate that profitability, solvability and institutional ownership have an influence on firm value while liquidity, firm size, dividend policy, and managerial ownership have no effect on firm value.